Creation and Validation of a Shorthand Knee MRI Bone Age Assessment Tool as an Alternative for Skeletal Maturity Assessment (203). Issue 10 (31st October 2021) - Politzer, Cary; Bomar, James; Pehlivan, Hakan; Gurusamy, Pradyumna; Edmonds, Eric; Pennock, Andrew
Objectives: In managing pediatric knee conditions, an accurate bone age assessment is often critical for diagnostic, prognostic, and treatment purposes. Historically, the Greulich and Pyle Atlas (hand atlas) has been the gold standard bone age assessment tool. In 2013, a shorthand bone age assessment tool based on this atlas (hand shorthand) was established as a simpler and more efficient alternative. Recently, a knee MRI bone age atlas (MRI atlas) was created potentially to circumvent the need for a left hand radiograph. Our objective is to create a shorthand version of the magnetic resonance imaging atlas. Methods: A shorthand bone age method (Figure 1) was created utilizing the previously published MRI atlas, which utilizes several criteria that are visualized across a series of images. The MRI shorthand draws on the most characteristic criteria for each age that is best observed on a single MR image. For validation, we performed a retrospective assessment of skeletally immature patients that had a knee MRI and left hand radiograph within four weeks. Four readers who were familiar with the hand atlas, hand shorthand, MRI atlas, and MRI shorthand read each of the images in a blinded fashion. Inter- and intra-observer reliability was evaluated using intraclass correlation coefficient (ICC), variability among observers was evaluated using percent agreement. Results: 26 patients with a mean age of 13.6 years (range 9.0-16.9) met the inclusion criteria. The intra- and inter-observer reliability of all four assessment tools was excellent (ICC ≥ 0.8, p<0.001) (Table 1). When comparing the MRI shorthand to the MRI atlas, there was excellent agreement (ICC = 0.974), whereas the hand shorthand compared to the hand atlas had good agreement (ICC = 0.765). The MRI shorthand also had perfect agreement in 58% of reads among all four readers and 96% of reads had agreement within 1 year, whereas the hand shorthand had perfect agreement in 32% of reads and 77% agreement within 1 year (Table 2). Conclusions: The MRI shorthand is a simple and efficient means of assessing skeletal maturity of adolescent patients with a knee MRI. This bone age assessment technique has inter-observer and intra-observer reliability equivalent or better than the standard means utilizing a left hand radiograph.